The role of service firms in societal health: the case for symbiotic value. (1st October 2020) - Aksoy, Lerzan; Alkire (née Nasr), Linda; Kandampully, Jay; Kemppainen, Laura; Kong, Lu; McClelland, Laura E.
Abstract : Purpose: The purpose of this study is to highlight the role that service firms can play to improve societal health and create symbiotic value, defined as value created as a result of collaborative relationships between the firm, its employees, customers and the communities in which it operates. Design/methodology/approach: This manuscript examines the case of Millennials as they make up a dominant portion of the current workforce in society and proposes a conceptual framework for symbiotic value creation. Findings: This study identifies the need to develop supporting mechanisms for the growing role of Millennials as employees and members of society that ultimately, in turn, create symbiotic value. Originality/value: The paper proposes an integrative framework beyond the traditional and siloed examination of linkages between employee, customer, firm and society, creating new opportunities for extending a service theory and practice.